Motivational Factors of Impulse Purchase Behaviour: A Comparison between Gender, Online and Offline Context - Tangsiri, Tanaphan (2016)
As a result of an increase in internet access throughout the world, more and more consumers have either joined or experienced e-commerce market. Impulse purchase behaviour has been seen as a revenue driver for many businesses and this behaviour should be further investigated to understand consumer and continuously develop selling medium to improve businesses performance. In this dissertation, the degree and magnitude of motivational factors between online and offline stores are being investigated to see whether which platform is able to satisfy motivation factors that cause consumer to shop on impulse. Furthermore, gender effect is also been investigated to see whether which gender will be more likely to be motivated to shop on impulse both online and offline. The motivational factors that this dissertation proposed consist of the motivation to satisfy hedonic need, social needs, and the perceive accuracy of purchase decision making.